Tomato (Solanum lycopersicum L.) SlIPT3 and SlIPT4 isopentenyltransferases mediate salt stress response in tomato - Žižková, Eva; Dobrev, Petre I; Muhovski, Yordan; Hošek, Petr; Hoyerová, Klára; Haisel, Daniel; Procházková, Dagmar; Lutts, Stanley; Motyka, Václav; Hichri, Imène (BMC plant biology, 2015)
BACKGROUND: Cytokinins (CKs) are involved in response to various environmental cues, including salinity. It has been previously reported that enhancing CK contents improved salt stress tolerance in tomato. However, the underlying mechanisms of CK metabolism and signaling under salt stress conditions remain to be deciphered. RESULTS: Two tomato isopentenyltransferases, SlIPT3 and SlIPT4, were characterized in tomato and Arabidopsis. Both proteins displayed isopentenyltransferase (IPT) activity in vitro, while their encoding genes exhibited different spatio-temporal expression patterns during tomato plant development. SlIPT3 and SlIPT4 were affected by the endogenous CK status, tightly connected with CKs feedback regulation, as revealed by hormonal treatements. In response to salt stress, SlIPT3 and SlIPT4 were strongly repressed in tomato roots, and differently affected in young and old leaves. SlIPT3 overexpression in tomato resulted in high accumulation of different CK metabolites, following modifications of CK biosynthesis-, signaling- and degradation-gene expression. In addition, 35S::SlIPT3 tomato plants displayed improved tolerance to salinity consecutive to photosynthetic pigments and K(+)/Na(+) ratio retention. Involvement of SlIPT3 and SlIPT4 in salt stress response was also observed in Arabidopsis ipt3 knock-out complemented plants, through maintenance of CK homeostasis. CONCLUSIONS: SlIPT3 and SlIPT4 are functional IPTs encoded by differently expressed genes, distinctively taking part in the salinity response. The substantial participation of SlIPT3 in CK metabolism during salt stress has been determined in 35S::SlIPT3 tomato transformants, where enhancement of CKs accumulation significantly improved plant tolerance to salinity, underlining the importance of this phytohormone in stress response.
Keywords: Cytokinins; Salt Tolerance; Arabidopsis; Alkyl and Aryl Transferases; geneticky modifikované rostliny; alkyltransferasy a aryltransferasy; Gene Expression Regulation, Plant; regulace genové exprese u rostlin; tolerance k soli; Plants, Genetically Modified; cytokininy; Solanum lycopersicum